2.1.14 Problem 14
Internal
problem
ID
[9085]
Book
:
Second
order
enumerated
odes
Section
:
section
1
Problem
number
:
14
Date
solved
:
Monday, January 27, 2025 at 05:32:21 PM
CAS
classification
:
[[_2nd_order, _missing_x], _Liouville, [_2nd_order, _reducible, _mu_xy]]
Solve
\begin{align*} y^{\prime \prime }+{y^{\prime }}^{2}&=0 \end{align*}
Solved as second order missing x ode
Time used: 0.197 (sec)
This is missing independent variable second order ode. Solved by reduction of order by using
substitution which makes the dependent variable \(y\) an independent variable. Using
\begin{align*} y' &= p \end{align*}
Then
\begin{align*} y'' &= \frac {dp}{dx}\\ &= \frac {dp}{dy}\frac {dy}{dx}\\ &= p \frac {dp}{dy} \end{align*}
Hence the ode becomes
\begin{align*} p \left (y \right ) \left (\frac {d}{d y}p \left (y \right )\right )+p \left (y \right )^{2} = 0 \end{align*}
Which is now solved as first order ode for \(p(y)\).
Factoring the ode gives these factors
\begin{align*}
\tag{1} p &= 0 \\
\tag{2} p^{\prime }+p &= 0 \\
\end{align*}
Now each of the above equations is solved in
turn.
Solving equation (1)
Solving for \(p\) from
\begin{align*} p = 0 \end{align*}
Solving gives \(p = 0\)
Solving equation (2)
Integrating gives
\begin{align*} \int -\frac {1}{p}d p &= dy\\ -\ln \left (p \right )&= y +c_1 \end{align*}
Singular solutions are found by solving
\begin{align*} -p&= 0 \end{align*}
for \(p\). This is because we had to divide by this in the above step. This gives the following
singular solution(s), which also have to satisfy the given ODE.
\begin{align*} p = 0 \end{align*}
Solving for \(p\) gives
\begin{align*}
p &= 0 \\
p &= {\mathrm e}^{-y -c_1} \\
\end{align*}
For solution (1) found earlier, since \(p=y^{\prime }\) then we now have a new first order
ode to solve which is
\begin{align*} y^{\prime } = 0 \end{align*}
Since the ode has the form \(y^{\prime }=f(x)\), then we only need to integrate \(f(x)\).
\begin{align*} \int {dy} &= \int {0\, dx} + c_2 \\ y &= c_2 \end{align*}
For solution (2) found earlier, since \(p=y^{\prime }\) then we now have a new first order ode to solve which is
\begin{align*} y^{\prime } = {\mathrm e}^{-y-c_1} \end{align*}
Integrating gives
\begin{align*} \int {\mathrm e}^{y +c_1}d y &= dx\\ {\mathrm e}^{y +c_1}&= x +c_3 \end{align*}
Solving for \(y\) gives
\begin{align*}
y &= -c_1 +\ln \left (x +c_3 \right ) \\
\end{align*}
Will add steps showing solving for IC soon.
Summary of solutions found
\begin{align*}
y &= c_2 \\
y &= -c_1 +\ln \left (x +c_3 \right ) \\
\end{align*}
Solved as second order missing y ode
Time used: 0.076 (sec)
This is second order ode with missing dependent variable \(y\). Let
\begin{align*} u(x) &= y^{\prime } \end{align*}
Then
\begin{align*} u'(x) &= y^{\prime \prime } \end{align*}
Hence the ode becomes
\begin{align*} u^{\prime }\left (x \right )+u \left (x \right )^{2} = 0 \end{align*}
Which is now solved for \(u(x)\) as first order ode.
Integrating gives
\begin{align*} \int -\frac {1}{u^{2}}d u &= dx\\ \frac {1}{u}&= x +c_1 \end{align*}
Singular solutions are found by solving
\begin{align*} -u^{2}&= 0 \end{align*}
for \(u \left (x \right )\). This is because we had to divide by this in the above step. This gives the following
singular solution(s), which also have to satisfy the given ODE.
\begin{align*} u \left (x \right ) = 0 \end{align*}
Solving for \(u \left (x \right )\) gives
\begin{align*}
u \left (x \right ) &= 0 \\
u \left (x \right ) &= \frac {1}{x +c_1} \\
\end{align*}
In summary, these are the solution found for \(u(x)\)
\begin{align*}
u \left (x \right ) &= 0 \\
u \left (x \right ) &= \frac {1}{x +c_1} \\
\end{align*}
For solution \(u \left (x \right ) = 0\), since \(u=y^{\prime }\) then we
now have a new first order ode to solve which is
\begin{align*} y^{\prime } = 0 \end{align*}
Since the ode has the form \(y^{\prime }=f(x)\), then we only need to integrate \(f(x)\).
\begin{align*} \int {dy} &= \int {0\, dx} + c_2 \\ y &= c_2 \end{align*}
For solution \(u \left (x \right ) = \frac {1}{x +c_1}\), since \(u=y^{\prime }\) then we now have a new first order ode to solve which is
\begin{align*} y^{\prime } = \frac {1}{x +c_1} \end{align*}
Since the ode has the form \(y^{\prime }=f(x)\), then we only need to integrate \(f(x)\).
\begin{align*} \int {dy} &= \int {\frac {1}{x +c_1}\, dx}\\ y &= \ln \left (x +c_1 \right ) + c_3 \end{align*}
In summary, these are the solution found for \((y)\)
\begin{align*}
y &= c_2 \\
y &= \ln \left (x +c_1 \right )+c_3 \\
\end{align*}
Will add steps showing solving for IC
soon.
Summary of solutions found
\begin{align*}
y &= c_2 \\
y &= \ln \left (x +c_1 \right )+c_3 \\
\end{align*}
Maple step by step solution
\[ \begin {array}{lll} & {} & \textrm {Let's solve}\hspace {3pt} \\ {} & {} & \left (\frac {d}{d x}y \left (x \right )\right )^{2}+\frac {d^{2}}{d x^{2}}y \left (x \right )=0 \\ \bullet & {} & \textrm {Highest derivative means the order of the ODE is}\hspace {3pt} 2 \\ {} & {} & \frac {d^{2}}{d x^{2}}y \left (x \right ) \\ \bullet & {} & \textrm {Make substitution}\hspace {3pt} u =\frac {d}{d x}y \left (x \right )\hspace {3pt}\textrm {to reduce order of ODE}\hspace {3pt} \\ {} & {} & u \left (x \right )^{2}+\frac {d}{d x}u \left (x \right )=0 \\ \bullet & {} & \textrm {Solve for the highest derivative}\hspace {3pt} \\ {} & {} & \frac {d}{d x}u \left (x \right )=-u \left (x \right )^{2} \\ \bullet & {} & \textrm {Separate variables}\hspace {3pt} \\ {} & {} & \frac {\frac {d}{d x}u \left (x \right )}{u \left (x \right )^{2}}=-1 \\ \bullet & {} & \textrm {Integrate both sides with respect to}\hspace {3pt} x \\ {} & {} & \int \frac {\frac {d}{d x}u \left (x \right )}{u \left (x \right )^{2}}d x =\int \left (-1\right )d x +\mathit {C1} \\ \bullet & {} & \textrm {Evaluate integral}\hspace {3pt} \\ {} & {} & -\frac {1}{u \left (x \right )}=\mathit {C1} -x \\ \bullet & {} & \textrm {Solve for}\hspace {3pt} u \left (x \right ) \\ {} & {} & u \left (x \right )=-\frac {1}{\mathit {C1} -x} \\ \bullet & {} & \textrm {Solve 1st ODE for}\hspace {3pt} u \left (x \right ) \\ {} & {} & u \left (x \right )=-\frac {1}{\mathit {C1} -x} \\ \bullet & {} & \textrm {Make substitution}\hspace {3pt} u =\frac {d}{d x}y \left (x \right ) \\ {} & {} & \frac {d}{d x}y \left (x \right )=-\frac {1}{\mathit {C1} -x} \\ \bullet & {} & \textrm {Integrate both sides to solve for}\hspace {3pt} y \left (x \right ) \\ {} & {} & \int \left (\frac {d}{d x}y \left (x \right )\right )d x =\int -\frac {1}{\mathit {C1} -x}d x +\mathit {C2} \\ \bullet & {} & \textrm {Compute integrals}\hspace {3pt} \\ {} & {} & y \left (x \right )=\ln \left (\mathit {C1} -x \right )+\mathit {C2} \end {array} \]
Maple trace
`Methods for second order ODEs:
--- Trying classification methods ---
trying 2nd order Liouville
<- 2nd_order Liouville successful`
Maple dsolve solution
Solving time : 0.011
(sec)
Leaf size : 10
dsolve(diff(diff(y(x),x),x)+diff(y(x),x)^2 = 0,y(x),singsol=all)
\[
y = \ln \left (c_{1} x +c_{2} \right )
\]
Mathematica DSolve solution
Solving time : 0.191
(sec)
Leaf size : 15
DSolve[{D[y[x],{x,2}]+(D[y[x],x])^2==0,{}},y[x],x,IncludeSingularSolutions->True]
\[
y(x)\to \log (x-c_1)+c_2
\]